Oil-based thermal energy storage medium

By using specific ratios of oils and additives in oil-based thermal energy storage media, and using hydropurification and solid catalytic desulfurization technologies, the shortcomings of existing heat storage media in specific heat capacity, oxidation stability and thermal stability are solved. Achieve efficient and stable thermal energy storage.

CN118562456BActive Publication Date: 2025-02-14JILIN HENGSHENG CHEM
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410475298.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-19
Publication Date
2025-02-14
Estimated Expiration
2044-04-19

AI Technical Summary

Technical Problem

Among the existing heat storage technologies, water storage has a small heat density and a large area, molten salt heat storage is easy to solidify, corrodes the pipes, and has high control costs. It is difficult to adjust the preparation process of oil-based energy storage liquid to improve its specific heat capacity, oxidation stability and Thermal stability.

Method used

Using 65 to 85 parts of Class III base oil, 1 to 3 parts of composite additives, 1 to 3 parts of antioxidants, 5 parts of alkyl naphthalene and no more than 10 parts of polyαolefins, through hydropurification process, solid catalyst, solid The use of desulfurization agents is used to prepare an oil-based thermal energy storage medium.

Benefits of technology

The specific heat capacity, oxidation resistance and thermal stability of the oil-based thermal energy storage medium are improved, and the product has good thermal stability, high specific heat capacity, low sulfur content and excellent oxidation stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004800318330000101
    Figure BDA0004800318330000101
  • Figure BDA0004800318330000111
    Figure BDA0004800318330000111
  • Figure BDA0004800318330000112
    Figure BDA0004800318330000112
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of thermal energy storage media, and in particular to an oil-based thermal energy storage medium, comprising the following raw materials in parts by weight: 65-85 parts of Class III base oil, 1-3 parts of composite additives, 1-3 parts of antioxidants, 5 parts of alkyl naphthalene, and no more than 10 parts of polyalphaolefins; the invention introduces Co and La elements into a solid catalyst, and in the presence of the Co and La elements, in a prepared hydrogenation solid catalyst, Co particles have a smaller particle size, stronger dispersibility, better stability on a carrier, and more abundant electrons; since alumina itself is acidic, as a solid catalyst, it is easy to cause C-C bond breakage during hydrogenation, and the addition of Co and La elements increases the basicity of the catalyst, which to a certain extent avoids the C-C bond breakage caused by the acidic carrier, so that the solid catalyst has better properties in the hydrogenation reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal energy storage medium preparation, and in particular to an oil-based thermal energy storage medium. Background Art

[0002] In the heating season, the vast urban areas in northern my country use small coal-fired boilers and stoves for heating, which causes serious winter air pollution and is not easy to restore and control. Therefore, how to apply heat storage heating technology in northern China is of great significance.

[0003] According to the different heat-carrying materials of the heat storage equipment, the current heat storage technologies include water heat storage and molten salt heat storage technology;

[0004] Water heat storage technology is to store heat energy in the form of hot water. The temperature range of normal pressure heat storage is generally 35℃~85℃. The disadvantage is that the energy storage density is small and the floor space is large. The temperature of pressurized water heat storage is generally 120℃~150℃, which requires a pressure container, has certain safety risks, and the equipment cost is relatively high.

[0005] The molten salt heat storage technology converts cheap electricity into heat energy through electric heaters, raising the temperature of the molten salt and storing it in a high-temperature molten salt tank. When heat energy needs to be supplied to the outside, the high-temperature molten salt releases the stored heat in the heat exchanger. The operating temperature of the molten salt can reach 560 degrees. However, the most important thing during use is that the molten salt is easy to solidify and will corrode the pipes. The operating system is very complex and the control cost is also high.

[0006] At present, the application of oil as energy storage fluid is becoming more and more extensive. However, how to adjust the preparation process of oil-based energy storage fluid and then control the properties of oil-based energy storage fluid so that it has good specific heat capacity, oxidation stability and thermal stability when used as energy storage fluid has become a problem to be solved. Summary of the invention

[0007] The object of the present invention is to provide an oil-based thermal energy storage medium to solve the above problems.

[0008] In order to achieve the above objectives, the following technical solutions are provided:

[0009] An oil-based thermal energy storage medium, the oil-based thermal energy storage medium comprising the following raw materials in parts by weight: 65 to 85 parts of Class III base oil, 1 to 3 parts of composite additives, 1 to 3 parts of antioxidants, 5 parts of alkyl naphthalene, and no more than 10 parts of polyalphaolefin;

[0010] The composite additive is 2,6-di-tert-butyl-α-dimethylamino-p-cresol and a copolymer of dodecyl acrylate and 1-decene; the kinematic viscosity of the polyalphaolefin at 100°C is 8 to 10 mm 2 / s;

[0011] The oil-based thermal energy storage medium is made by the following method:

[0012] To prepare solid catalyst and solid desulfurizer, take the crude oil after hydrocracking treatment, at a temperature of 300-320°C, a pressure of 10.5-15.5MPa, a volume ratio of hydrogen to crude oil of 800-1200, the maximum temperature in the hydrogenation tower during the reaction is not higher than 340°C, and the volume space velocity is 15.5-21.5h -1 Under the following conditions, the crude oil, hydrogen, solid catalyst and solid desulfurizing agent are contacted and hydrogenated, and then the liquid product is taken, and composite additives, antioxidants, alkyl naphthalene and poly-alpha olefin are added to obtain an oil-based thermal energy storage medium.

[0013] Preferably, the preparation method of the solid catalyst is as follows:

[0014] Dissolve 0.6-1.0 mol Mg(NO3)2·6H2O, 0.2-0.6 mol Co(NO3)2·6H2O, 0.015-0.045 mol La(NO3)3·6H2O, 0.2-0.6 mol AI(NO3)3·9H2O and 2.5-3 mol urea in 300 mL of deionized water to prepare a mixed salt solution, transfer the solution to a flask, place the flask containing the mixed salt solution in a heat-insulating and heating magnetic stirrer, stir at 80°C for 10 h, take out the flask, shake for 3 min, age for 6 h, and then filter to obtain a precipitate, wash the precipitate with deionized water, and then place the precipitate after washing with deionized water in a vacuum oven and dry it at 90°C for 12 h to obtain a catalyst precursor, calcine the catalyst precursor at 700°C in air for 5 h, and take out the solid to obtain a solid catalyst;

[0015] The solid desulfurizer includes active components and a carrier. The carrier is an X-type molecular sieve. Based on the mass of the carrier, the active components include 45-50 weight % of ZnO, 2-5 weight % of TiO2, 5-10 weight % of Cr2O3, and 5-10 weight % of NiO.

[0016] Preferably, the specific surface area of ​​the carrier is 280 m 2 / g, pore volume is 0.5cm 3 / g.

[0017] Preferably, the preparation method of the solid desulfurizer is as follows:

[0018] Take zinc nitrate and add it to a mixed solvent of ethylene glycol and acetone, add deionized water and X-type molecular sieve while stirring, knead and extrude strips, dry at 110-130°C for 6 hours, then transfer to a muffle furnace, and roast at 530-570°C for 2 hours in an air atmosphere to obtain strips, ball mill and sieve to obtain a solid, mix the solid in a solution containing TiO2, Cr2O3 and NiO components, beat to obtain a slurry, spray dry, and roast at 760-820°C for 8-10 hours in an air atmosphere to obtain a solid desulfurizer.

[0019] Preferably, based on the total weight percentage of the antioxidant, the antioxidant includes 5% to 15% of phenolic antioxidants, 15% to 25% of amine antioxidants, 20% to 35% of ester antioxidants, and 25% to 60% of emulsifiers.

[0020] Preferably, the preparation method of the antioxidant is as follows:

[0021] Add phenolic antioxidants, amine antioxidants and ester antioxidants into a beaker, stir and heat until the temperature reaches 80-85°C, add emulsifier, stir for 3-5 minutes with a high-speed shearing machine, emulsify for 3-5 minutes, continue stirring with the high-speed shearing machine for 3-5 minutes to obtain antioxidant.

[0022] Preferably,

[0023] The phenolic antioxidant is 4,4'-methylenebis(2,6-di-tert-butylphenol);

[0024] The amine antioxidant is 4,4'-bis(α,α-dimethylbenzyl)diphenylamine;

[0025] The ester antioxidant is hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate);

[0026] The emulsifier is an alkyl glycoside.

[0027] The beneficial effects of the present invention are:

[0028] 1. The present invention introduces Co and La elements into the solid catalyst. In the presence of the two, the Co particles in the prepared hydrogenation solid catalyst have smaller particle size, stronger dispersibility, better stability on the carrier, and more abundant electrons. Since alumina itself is acidic, it is easy to cause CC bond rupture during the hydrogenation process as a solid catalyst. The addition of Co and La elements increases the basicity of the catalyst, which to a certain extent avoids the CC bond rupture caused by the acidic carrier, making the solid catalyst more excellent in the hydrogenation reaction.

[0029] At the same time, by using X-type molecular sieve as carrier and ZnO as main active component, TiO2, Cr2O3, NiO and other components are added to improve the penetration sulfur capacity, further improving the desulfurization effect of solid desulfurizer;

[0030] The present invention uses a unique solid catalyst and a solid desulfurizer to treat the oil-based thermal energy storage medium, and additionally adds an antioxidant, 2,6-di-tert-butyl-α-dimethylamino-p-cresol, a copolymer of dodecyl acrylate and 1-decene, alkyl naphthalene and poly-α-olefin to improve the specific heat capacity, antioxidant performance and thermal stability of the oil-based thermal energy storage medium. The product oil-based thermal energy storage medium has good thermal stability, high specific heat capacity, low sulfur content and excellent oxidation stability. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the schematic diagrams in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1: A method for preparing a solid catalyst is as follows:

[0033] 0.6 mol Mg(NO3)2·6H2O, 0.2 mol Co(NO3)2·6H2O, 0.015 mol La(NO3)3·6H2O, 0.2 mol AI(NO3)3·9H2O and 2.5 mol urea were dissolved in 300 mL deionized water to prepare a mixed salt solution, which was transferred to a flask. The flask containing the mixed salt solution was placed in a heat-insulating and heating magnetic stirrer and stirred at 80°C for 10 h. The flask was taken out and vibrated for 3 min. After aging for 6 h, the precipitate was filtered to obtain a precipitate. The precipitate was washed with deionized water, and then the precipitate after washing with deionized water was placed in a vacuum oven and dried at 90°C for 12 h to obtain a catalyst precursor. The catalyst precursor was calcined in air at 700°C for 5 h, and a solid was obtained to obtain a solid catalyst.

[0034] A method for preparing a solid desulfurizer is as follows:

[0035] Take 86g of zinc nitrate and add it to a mixed solvent of 50mL of ethylene glycol and acetone, add 100mL of deionized water and 80g of X-type molecular sieve while stirring, knead and squeeze, dry at 110°C for 6h, transfer to a muffle furnace, calcine at 530°C for 2h in an air atmosphere to obtain a strip body, ball mill and sieve to obtain a solid, mix the solid in a solution containing 4g of TiO2, 8g of Cr2O3, and 8g of NiO components, beat to obtain a slurry, spray dry, and calcine at 760°C for 8h in an air atmosphere to obtain a solid desulfurizer;

[0036] A method for preparing an antioxidant is as follows:

[0037] 2.5 g of 4,4'-methylenebis(2,6-di-tert-butylphenol), 7.5 g of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine and 10 g of hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) were added to a beaker, stirred and heated until the temperature reached 80°C, 30 g of alkyl glycoside was added, stirred for 3 min using a high-speed shearing machine, emulsified for 3 min, and continued to stir for 3 min using a high-speed shearing machine to obtain an antioxidant;

[0038] A method for preparing an oil-based thermal energy storage medium is as follows:

[0039] At a temperature of 300°C, a pressure of 10.5 MPa, a volume ratio of hydrogen to crude oil of 800, a maximum temperature in the hydrogenation tower of no more than 340°C during the reaction, and a volume space velocity of 15.5 h -1 Under the following conditions, the crude oil, hydrogen, solid catalyst and solid desulfurizing agent are contacted and hydrogenated, and then the liquid product is taken, and 2,6-di-tert-butyl-α-dimethylamino-p-cresol, a copolymer of dodecyl acrylate and 1-decene, an antioxidant, alkyl naphthalene and poly-α-olefin are added to obtain an oil-based thermal energy storage medium.

[0040] Example 2: A method for preparing a solid catalyst is as follows:

[0041] 0.8 mol Mg(NO3)2·6H2O, 0.4 mol Co(NO3)2·6H2O, 0.03 mol La(NO3)3·6H2O, 0.4 mol AI(NO3)3·9H2O and 2.7 mol urea were dissolved in 300 mL deionized water to prepare a mixed salt solution, which was transferred to a flask. The flask containing the mixed salt solution was placed in a heat-insulating and heating magnetic stirrer and stirred at 80°C for 10 h. The flask was taken out and vibrated for 3 min. After aging for 6 h, a precipitate was obtained by filtering. The precipitate was washed with deionized water, and then the precipitate after washing with deionized water was placed in a vacuum oven and dried at 90°C for 12 h to obtain a catalyst precursor. The catalyst precursor was calcined in air at 700°C for 5 h, and a solid was obtained to obtain a solid catalyst.

[0042] A method for preparing a solid desulfurizer is as follows:

[0043] Take 90g zinc nitrate and add it to a mixed solvent of 50mL ethylene glycol and acetone, add 100mL deionized water and 80g X-type molecular sieve while stirring, knead and squeeze, dry at 120℃ for 6h, transfer to a muffle furnace, calcine at 550℃ for 2h in air atmosphere to obtain a strip body, ball mill and sieve to obtain a solid, mix the solid with a solution containing 2.4g TiO2, 5.6g Cr2O3 and 5.6g NiO components, beat to obtain a slurry, spray dry, and calcine at 780℃ for 9h in air atmosphere to obtain a solid desulfurizer;

[0044] A method for preparing an antioxidant is as follows:

[0045] 5 g of 4,4'-methylenebis(2,6-di-tert-butylphenol), 10 g of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine and 13.5 g of hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) were added to a beaker, stirred and heated until the temperature reached 83°C, 21.5 g of alkyl glycoside was added, stirred for 4 min using a high-speed shearing machine, emulsified for 4 min, and stirred for 4 min using a high-speed shearing machine to obtain an antioxidant;

[0046] A method for preparing an oil-based thermal energy storage medium is as follows:

[0047] At a temperature of 310°C, a pressure of 13.5 MPa, a volume ratio of hydrogen to crude oil of 1000, a maximum temperature in the hydrogenation tower of no more than 340°C during the reaction, and a volume space velocity of 18.5 h -1 Under the following conditions, the crude oil, hydrogen, solid catalyst and solid desulfurizing agent are contacted and hydrogenated, and then the liquid product is taken, and 2,6-di-tert-butyl-α-dimethylamino-p-cresol, a copolymer of dodecyl acrylate and 1-decene, an antioxidant, alkyl naphthalene and poly-α-olefin are added to obtain an oil-based thermal energy storage medium.

[0048] Example 3: A method for preparing a solid catalyst is as follows:

[0049] 1.0 mol Mg(NO3)2·6H2O, 0.6 mol Co(NO3)2·6H2O, 0.045 mol La(NO3)3·6H2O, 0.6 mol AI(NO3)3·9H2O and 3 mol urea were dissolved in 300 mL deionized water to prepare a mixed salt solution, which was transferred to a flask. The flask containing the mixed salt solution was placed in a heat-insulating and heating magnetic stirrer and stirred at 80°C for 10 h. The flask was taken out and vibrated for 3 min. After aging for 6 h, the precipitate was filtered to obtain a precipitate. The precipitate was washed with deionized water, and then the precipitate after washing with deionized water was placed in a vacuum oven and dried at 90°C for 12 h to obtain a catalyst precursor. The catalyst precursor was calcined in air at 700°C for 5 h, and a solid was obtained to obtain a solid catalyst.

[0050] A method for preparing a solid desulfurizer is as follows:

[0051] Take 93g of zinc nitrate and add it to a mixed solvent of 50mL of ethylene glycol and acetone, add 100mL of deionized water and 80g of X-type molecular sieve while stirring, knead and squeeze, dry at 130°C for 6h, transfer to a muffle furnace, calcine at 570°C for 2h in an air atmosphere to obtain a strip body, ball mill and sieve to obtain a solid, mix the solid in a solution containing 1.6g of TiO2, 4g of Cr2O3, and 4g of NiO components, beat to obtain a slurry, spray dry, and calcine at 820°C for 10h in an air atmosphere to obtain a solid desulfurizer;

[0052] A method for preparing an antioxidant is as follows:

[0053] 7.5 g of 4,4'-methylenebis(2,6-di-tert-butylphenol), 12.5 g of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine and 17.5 g of hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) were added to a beaker, stirred and heated until the temperature reached 85°C, 12.5 g of alkyl glycoside was added, stirred for 5 min using a high-speed shearing machine, emulsified for 5 min, and stirred for 5 min using a high-speed shearing machine to obtain an antioxidant;

[0054] A method for preparing an oil-based thermal energy storage medium is as follows:

[0055] At a temperature of 320°C, a pressure of 15.5 MPa, a volume ratio of hydrogen to crude oil of 1200, a maximum temperature in the hydrogenation tower of no more than 340°C during the reaction, and a volume space velocity of 21.5 h -1 Under the following conditions, the crude oil, hydrogen, solid catalyst and solid desulfurizing agent are contacted and hydrogenated, and then the liquid product is taken, and 2,6-di-tert-butyl-α-dimethylamino-p-cresol, a copolymer of dodecyl acrylate and 1-decene, an antioxidant, alkyl naphthalene and poly-α-olefin are added to obtain an oil-based thermal energy storage medium.

[0056] Comparative Example 1: The preparation method of the solid catalyst, solid desulfurizer and antioxidant is the same as that of Example 1;

[0057] A method for preparing an oil-based thermal energy storage medium is as follows:

[0058] At a temperature of 300°C, a pressure of 10.5 MPa, a volume ratio of hydrogen to crude oil of 800, a maximum temperature in the hydrogenation tower of no more than 340°C during the reaction, and a volume space velocity of 15.5 h -1 Under the following conditions, the crude oil, hydrogen, solid catalyst and solid desulfurizing agent are contacted and hydrogenated, and then the liquid product is taken, and an antioxidant, alkyl naphthalene, poly-alpha olefin and antioxidant 245 are added to obtain an oil-based thermal energy storage medium.

[0059] Comparative Example 2: The preparation method of the solid desulfurizer and antioxidant is the same as that of Example 1;

[0060] A method for preparing an oil-based thermal energy storage medium is as follows:

[0061] At a temperature of 300°C, a pressure of 10.5 MPa, a volume ratio of hydrogen to crude oil of 800, a maximum temperature in the hydrogenation tower of no more than 340°C during the reaction, and a volume space velocity of 15.5 h -1 Under the following conditions, the crude oil, hydrogen, solid desulfurizing agent and a solid catalyst with aluminum oxide as a carrier and tungsten oxide as an active component are contacted for hydrogenation refining, and then the liquid product is taken, and 2,6-di-tert-butyl-α-dimethylamino-p-cresol, a copolymer of dodecyl acrylate and 1-decene, an antioxidant, alkyl naphthalene and poly-α-olefin are added to obtain an oil-based thermal energy storage medium.

[0062] Comparative Example 3: The preparation method of the solid catalyst and antioxidant is the same as that of Example 1;

[0063] A method for preparing an oil-based thermal energy storage medium is as follows:

[0064] At a temperature of 300°C, a pressure of 10.5 MPa, a volume ratio of hydrogen to crude oil of 800, a maximum temperature in the hydrogenation tower of no more than 340°C during the reaction, and a volume space velocity of 15.5 h -1 Under the following conditions, the crude oil, hydrogen, a solid catalyst and methyl monoethanolamine are contacted for hydrogenation refining, and then the liquid product is taken, and 2,6-di-tert-butyl-α-dimethylamino-p-cresol, a copolymer of dodecyl acrylate and 1-decene, an antioxidant, alkyl naphthalene and poly-α-olefin are added to obtain an oil-based thermal energy storage medium.

[0065] Comparative Example 4: The preparation method of the solid catalyst and the solid desulfurizing agent is the same as that of Example 1;

[0066] A method for preparing an oil-based thermal energy storage medium is as follows:

[0067] At a temperature of 300°C, a pressure of 10.5 MPa, a volume ratio of hydrogen to crude oil of 800, a maximum temperature in the hydrogenation tower of no more than 340°C during the reaction, and a volume space velocity of 15.5 h -1 Under the following conditions, the crude oil, hydrogen, solid catalyst and solid desulfurizing agent are contacted and hydrogenated, and then the liquid product is taken and 2,6-di-tert-butyl-α-dimethylamino-p-cresol, a copolymer of dodecyl acrylate and 1-decene, alkyl naphthalene, poly-α-olefin and antioxidant 168 are added to obtain an oil-based thermal energy storage medium.

[0068] Performance Testing:

[0069] Thermal stability test: The thermal stability of the oil-based thermal energy storage media prepared in Examples 1-3 and Comparative Examples 1-4 was tested according to GB / T23800, 320°C, 720h conditions;

[0070] Table 1: Thermal stability test results

[0071]

[0072]

[0073] It can be seen from the data in Table 1 that the oil-based thermal energy storage medium prepared in Examples 1-3 of the present invention has the characteristics of low content of gaseous decomposition products, low boiling substances, high boiling substances, and non-evaporable substances, and low deterioration rate. In Table 1, the content of gaseous decomposition products, low boiling substances, high boiling substances, and non-evaporable substances in Example 1 is not greater than the corresponding substance content in Examples 2 and 3, and the deterioration rate of Example 1 is the lowest; Comparative Example 1 is compared with Example 1, in which 2,6-di-tert-butyl-α-dimethylamino-p-cresol and the copolymer of dodecyl acrylate and 1-decene are not added, and the measured gaseous decomposition products, low boiling substances, high boiling substances, non-evaporable substances and deterioration rates are higher than those in Examples 1- 3 is not significantly improved; Comparative Example 2 is compared with Example 1, the solid catalyst in Example 1 is not used, and the measured gas phase decomposition products, low boiling substances, high boiling substances, non-evaporable substances and deterioration rates are significantly improved compared with Examples 1-3; Comparative Example 3 is compared with Example 1, the solid desulfurizer in Example 1 is not used, and the measured gas phase decomposition products, low boiling substances, high boiling substances, non-evaporable substances and deterioration rates are significantly improved compared with Examples 1-3; Comparative Example 4 is compared with Example 1, the antioxidant in Example 1 is not used, and the measured gas phase decomposition products, low boiling substances, high boiling substances, non-evaporable substances and deterioration rates are not significantly improved compared with Examples 1-3;

[0074] Specific heat capacity test: The oil-based thermal energy storage media prepared in Examples 1-3 and Comparative Examples 1-4 were respectively measured for specific heat capacity at 20° C., 100° C. and 200° C. using a fluid specific heat measuring instrument;

[0075] Table 2: Specific heat capacity determination results

[0076]

[0077]

[0078] It can be seen from the data in Table 2 that the oil-based thermal energy storage medium prepared in Examples 1-3 of the present invention has the characteristic of high specific heat capacity. In Table 2, the specific heat capacity of Example 3 at 20°C, 100°C and 200°C is higher than that of Examples 1 and 2. Compared with Example 1, Comparative Example 1 does not add 2,6-di-tert-butyl-α-dimethylamino-p-cresol and the copolymer of dodecyl acrylate and 1-decene, and its specific heat capacity measured at 20°C, 100°C and 200°C is significantly lower than that of Examples 1-3. Compared with Example 1, Comparative Example 2 does not use the solid catalyst in Example 1, and its specific heat capacity measured at 20°C, 100°C and 200°C is significantly lower than that of Examples 1-3; Compared with Example 1, Comparative Example 3 does not use the solid desulfurizer in Example 1, and its specific heat capacity measured at 20°C, 100°C and 200°C is significantly lower than that of Examples 1-3; Compared with Example 1, Comparative Example 4 does not use the antioxidant in Example 1, and its specific heat capacity measured is significantly lower than that of Examples 1-3;

[0079] Sulfur content determination: The sulfur content of the oil-based thermal energy storage media prepared in Examples 1-3 and Comparative Examples 1-4 was determined using a high-sensitivity X-ray fluorescence spectrometer;

[0080] Table 3: Sulfur content determination results

[0081]

[0082]

[0083] It can be seen from the data in Table 3 that the oil-based thermal energy storage medium prepared in Examples 1-3 of the present invention has the characteristic of low sulfur content. In Table 3, the sulfur content of Example 2 is slightly higher than that of Examples 1 and 3; Compared with Example 1, Comparative Example 1 does not add 2,6-di-tert-butyl-α-dimethylamino-p-cresol and the copolymer of dodecyl acrylate and 1-decene, and the measured sulfur content is not significantly improved compared with Examples 1-3; Compared with Example 1, Comparative Example 2 does not use the solid catalyst in Example 1, and the measured sulfur content is improved compared with Examples 1-3; Compared with Example 1, Comparative Example 3 does not use the solid desulfurizer in Example 1, and the measured sulfur content is significantly improved compared with Examples 1-3; Compared with Example 1, Comparative Example 4 does not use the antioxidant in Example 1, and the measured sulfur content is not much different from that of Examples 1-3;

[0084] Oxidation stability test: The oil-based thermal energy storage media prepared in Examples 1-3 and Comparative Examples 1-4 were tested for oxidation stability according to NB / SH / T 0193, 175°C, 72h conditions;

[0085] Table 4: Oxidation stability test results

[0086]

[0087]

[0088] It can be seen from the data in Table 4 that the oil-based thermal energy storage medium prepared in Examples 1-3 of the present invention has the characteristics of low viscosity growth, low acid value increase, and low sediment, that is, good oxidation stability. In Table 4, Example 3 has the lowest viscosity growth and the least acid value increase; Comparative Example 1, compared with Example 1, does not add 2,6-di-tert-butyl-α-dimethylamino-p-cresol and the copolymer of dodecyl acrylate and 1-decene, and the measured viscosity growth is not significantly improved compared with Examples 1-3, and the acid value increase is not much different from that of Examples 1-3; the sediment is improved compared with Examples 1-3; Comparative Example 2, compared with Example 1, does not use the solid Compared with Example 1-3, the solid catalyst has a viscosity increase that is not significantly higher than that of Example 1-3, and the acid value increase is significantly higher than that of Example 1-3; the sediment is significantly higher than that of Example 1-3; Compared with Example 1, Comparative Example 3 does not use the solid desulfurizer in Example 1, and the viscosity increase measured is significantly higher than that of Example 1-3, and the acid value increase is significantly higher than that of Example 1-3; the sediment is significantly higher than that of Example 1-3; Compared with Example 1, Comparative Example 4 does not use the antioxidant in Example 1, and the viscosity increase measured is significantly higher than that of Example 1-3, and the acid value increase is not much different from that of Example 1-3; the sediment is significantly higher than that of Example 1-3.

[0089] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. An oil-based thermal energy storage medium, characterized in that: The oil-based thermal energy storage medium comprises the following raw materials in parts by weight: 65 to 85 parts of Class III base oil, 1 to 3 parts of composite additives, 1 to 3 parts of antioxidants, 5 parts of alkyl naphthalene, and no more than 10 parts of polyalphaolefin; The composite additive is 2,6-di-tert-butyl-α-dimethylamino-p-cresol and a copolymer of dodecyl acrylate and 1-decene; the kinematic viscosity of the polyalphaolefin at 100°C is 8-10mm 2 / s; The oil-based thermal energy storage medium is made by the following method: To prepare solid catalyst and solid desulfurizer, take the crude oil after hydrocracking treatment, at a temperature of 300-320°C, a pressure of 10.5-15.5MPa, a volume ratio of hydrogen to crude oil of 800-1200, the maximum temperature in the hydrogenation tower during the reaction is not higher than 340°C, and the volume space velocity is 15.5-21.5h -1 Under the following conditions, the crude oil, hydrogen, solid catalyst and solid desulfurizing agent are contacted and hydrogenated, and then the liquid product is taken, and composite additives, antioxidants, alkyl naphthalene and poly-alpha olefin are added to obtain the oil-based thermal energy storage medium; The preparation method of the solid catalyst is as follows: 0.6-1.0 mol Mg(NO3)2·6H2O, 0.2-0.6 mol Co(NO3)2·6H2O, 0.015-0.045 mol La(NO3)3·6H2O and 0.2-0.6 mol Al(NO3)3·9H2O and 2.5-3 mol urea are dissolved in 300 mL of deionized water to prepare a mixed salt solution, which is then transferred to a flask. The flask containing the mixed salt solution is then placed in a heat-insulating and heating magnetic stirrer and stirred at 80°C for 10 h. The flask is taken out and shaken for 3 min. After aging for 6 h, a precipitate is obtained by filtering. The precipitate is washed with deionized water, and then the precipitate after washing with deionized water is placed in a vacuum oven and dried at 90°C for 12 h to obtain a catalyst precursor. The catalyst precursor is calcined in air at 700°C for 5 h, and a solid is obtained to obtain a solid catalyst. The solid desulfurizer comprises an active component and a carrier, wherein the carrier is an X-type molecular sieve, and based on the mass of the carrier, the active component comprises 45-50 weight % of ZnO, 2-5 weight % of TiO2, 5-10 weight % of Cr2O3, and 5-10 weight % of NiO; The preparation method of the solid desulfurizer is as follows: Take zinc nitrate and add it to a mixed solvent of ethylene glycol and acetone, add deionized water and X-type molecular sieve while stirring, knead and squeeze, dry at 110-130°C for 6 hours, transfer to a muffle furnace, and roast at 530-570°C for 2 hours in an air atmosphere to obtain a strip body, ball mill and sieve to obtain a solid, mix the solid in a solution containing TiO2, Cr2O3, and NiO components, beat to obtain a slurry, spray dry, and roast at 760-820°C for 8-10 hours in an air atmosphere to obtain a solid desulfurizer; The preparation method of the antioxidant is as follows: Add phenolic antioxidants, amine antioxidants and ester antioxidants into a beaker, stir and heat until the temperature reaches 80-85°C, add emulsifier, stir for 3-5 minutes with a high-speed shearing machine, emulsify for 3-5 minutes, continue stirring with the high-speed shearing machine for 3-5 minutes to obtain antioxidant.

2. An oil-based thermal energy storage medium according to claim 1, characterized in that: The specific surface area of ​​the carrier is 280 m 2 / g, pore volume is 0.5cm 3 / g.

3. An oil-based thermal energy storage medium according to claim 2, characterized in that: Based on the total weight percentage of the antioxidant, the antioxidant includes 5% to 15% of phenol antioxidant, 15% to 25% of amine antioxidant, 20% to 35% of ester antioxidant and 25% to 60% of emulsifier.

4. The oil-based thermal energy storage medium according to claim 3, characterized in that: The phenolic antioxidant is 4,4'-methylenebis(2,6-di-tert-butylphenol); The amine antioxidant is 4,4'-bis(α,α-dimethylbenzyl)diphenylamine; The ester antioxidant is hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate); The emulsifier is an alkyl glycoside.

Citation Information

Patent Citations

  • Pre-reduced high-temperature synthesis gas methanation catalyst and preparation method thereof

    CN105233834A

  • Antioxidant for heat conduction oil and antioxidation method

    CN106978242A